The Important Moderation Fatwa Contemporary and Ijtihad - Marling, Nashirul Haq (Journal of Islamic Law El Madani, 2022)
Verify the eligibility of ijtihad, so that anyone who does not know the purpose, understands it and is able to access and know it, is not eligible for ijtihad. One of the most important principles and foundations that must be considered in applying the theory of sharia objectives in ijtihad and fatwas is the moderation approach. This study discusses "the importance of a moderation approach in contemporary fatwas and ijtihad". Researchers rely on an inductive approach as required by writing research in gathering scientific material. In the first chapter, the study discusses the introduction and methodological approaches. In the second chapter, the importance of a moderation approach in fatwa and ijtihad from its concept, evidence of its legitimacy and the extent to which it is considered in contemporary ijtihad and ijtihad. fatwa. The connotation of moderation cannot be separated from the meaning of justice, virtue, virtue, half-heartedness, togetherness, and mediation between the two parties. In achieving the meaning of moderation, it is not valid to give up unless it has two qualities; The first: alms or what shows it to be the best and fairest. The second: interface, whether it is sensory or moral. What is meant by moderation in a fatwa is a commendable condition that protects the mufti from excessive tendencies of both parties and negligence. Observing the principles and methods of moderation and moderation confirms its importance in scholars and ijtihad. So the muftis must maintain a moderation approach, namely mediating between ease and difficulty, and moderation between the extravagant and the puritanical so that the nation does not fall into trouble, shame and hardship. Then the third chapter discusses the components of the moderation approach in contemporary fatwa and ijtihad, which can be summarized as follows: First: balancing text and purpose. The second: balancing interests and real crimes. Third: The balance between wills and licenses. And the fourth: balancing between jealousy of the truth and mercy for creation.